The Difficulties of Teaching the subject of Skill and Social values in the first circle of the basic stage from teacher's perspectives - Rangin Sadeeq Bakr; Ameera Hseen Shareef (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
The aimed of this study is to investigate the obstacles to teaching the subject of skills and social values ​​in the first circle of the basic stage from teacher's perspectives, and to determine the effect of variables (gender, years of service) in determining obstacles. To achieve this goal of the study, applied descriptive approach and survey was prepared and it was confirmed. In terms of validity and reliability, which consists of (5) the basic field that relates to difficulties in the field of (teaching methods, teachers, students, curricula, and administrative capacity for education), the research tool was applied to a study sample consisting of teachers from the borders of the education center in the governorate Erbil is (95) teachers. This research reached these results. The presence of a group of obstacles in teaching skills and social values ​​precedes obstacles related to teachers. The results also showed that the gender variable had no effect on the differences in teachers’ responses to a survey, as the variable of years of service has an impact on the differences in the responses of teachers to a survey in identifying obstacles. In light of the results of the study, some recommendations were investigated. At the end of the research, the research suggested the obstacles to teaching the subject, skills, and social values ​​in the preparatory stage from the point of view of the teacher and the educational supervisor.